Fixed point theorems for generalised contractions in altering JS-metric space with graph - Alshammari, I.; Özel, C.; Gnanachandra, P.; Varunnya, X.M.J. (Carpathian Mathematical Publications, 2024)
Throughout this article, we propose an extension of the metric space due to M. Jleli and B. Samet (JS-metric space). This extension is made using the altering distance function, hence the name altering JS-metric. The idea of fixed points for the contraction mappings endowed with graph was first introduced by J. Jachymski in 2008. After that many researchers followed this idea and proposed various contraction mappings endowed with a graph. Motivated by these ideas, we have generalised some well-known contraction mappings in the literature that are endowed with a graph. Additionally, we have provided some fixed point results concerning these contractions in an altering JS-metric space.